2012
DOI: 10.2147/opth.s29431
|View full text |Cite
|
Sign up to set email alerts
|

Validation and verification of the OPI 2.0 System

Abstract: PurposeThe Ocular Protection Index (OPI) 2.0 System was developed to evaluate ocular surface protection under a natural blink pattern and normal visual conditions. The OPI 2.0 System implements fully automated software algorithms which provide a real-time measurement of corneal exposure (breakup area) for each interblink interval during a 1-minute video. Utilizing this method, the mean breakup area (MBA) and OPI 2.0 (MBA/interblink interval) were calculated and analyzed. The purpose of this study was to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…This is a result of significant strides in ocular surface biology research, and improvements in clinical assessment techniques such as, corneal staining, blink pattern analysis, and various measures of tear film stability 4,5. In two recent papers we described the stepwise development of our improved method of tear film analysis, which we have designated the ocular tear film analysis protocol OPI 2.0 (Ora, Inc. Andover MA, USA; patent pending) system 6,7. This method combines a number of optimized parameters with automated video data capture and analysis, to generate a more objective, quantitative measure of tear film dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is a result of significant strides in ocular surface biology research, and improvements in clinical assessment techniques such as, corneal staining, blink pattern analysis, and various measures of tear film stability 4,5. In two recent papers we described the stepwise development of our improved method of tear film analysis, which we have designated the ocular tear film analysis protocol OPI 2.0 (Ora, Inc. Andover MA, USA; patent pending) system 6,7. This method combines a number of optimized parameters with automated video data capture and analysis, to generate a more objective, quantitative measure of tear film dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was found that reduction and standardization of the quantity of fluorescein used, led to a shift of the reference values for TFBUT (to a mean value of 7 seconds for normal subjects, and 2.5 seconds for those with dry eye) 5. Similarly, our goal in developing the OPI 2.0 system was to enhance and streamline dry eye metrics by measuring tear film stability under conditions of natural, rather than forced stare blinking 6,7. Furthermore, by capturing the natural dynamics of the tear film with automated methods, it is possible to expand upon previous studies of the interaction between blinking and tear film behavior 8–13…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tear film stability and IBI, both assessments of drying on the ocular surface, were measured by the Ocular Protection Index (OPI) 2.0 System, an automated measure of ocular surface protection under normal blink pattern and normal visual conditions. 15 , 16 Video capture and analysis using the OPI 2.0 System allows for a calculation of mean corneal surface exposure, otherwise known as mean breakup area (MBA). Final endpoints were percent change in MBA and IBI in seconds.…”
Section: Methodsmentioning
confidence: 99%